Parabolic (φ, ξ, η, g, λ)-structures of second kind on hypersurfaces of dual metric 4-dimensional spaces - Baškienė, Angelė (Lietuvos matematikos rinkinys, 2002)
Parabolic metric (φ, ξ, η, g, λ)-structures of second kind on hypersurfaces of 4-dimensional dual metric space and its properties are investigated. Some examples of normal, integrable parabolic metric structures of second kind are given.